1989
DOI: 10.1073/pnas.86.8.2863
|View full text |Cite
|
Sign up to set email alerts
|

The human endothelin family: three structurally and pharmacologically distinct isopeptides predicted by three separate genes.

Abstract: Three distinct human endothelin-related genes were cloned by screening a genomic DNA library under a low hybridization stringency with a synthetic oligonucleotide probe encoding a portion of the endothelin sequence. Genomic Southern blot analysis with the same oligonucleotide probe showed three corresponding chromosomal loci not only in the human genome but also in porcine and rat genomes. The nucleotide sequences of the three human genes were highly conserved within the regions encoding the 21-residue (mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
1,100
3
44

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,270 publications
(1,161 citation statements)
references
References 28 publications
14
1,100
3
44
Order By: Relevance
“…NO may also be produced and released under the influence of stimuli such as acetylcholine, bradykinin, substance P, serotonin, and mechanical shear stresses 4 . The endothelium also produces endogenous vasoconstrictors, such as endothelin-1 (ET-1), which is particularly potent 4,14,15 . Human ET-1 is derived from pre-pro-ET-1 which is enzymatically cleaved to form big ET-1 which is further processed to form the active peptide by endothelin-converting enzyme 16 .…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…NO may also be produced and released under the influence of stimuli such as acetylcholine, bradykinin, substance P, serotonin, and mechanical shear stresses 4 . The endothelium also produces endogenous vasoconstrictors, such as endothelin-1 (ET-1), which is particularly potent 4,14,15 . Human ET-1 is derived from pre-pro-ET-1 which is enzymatically cleaved to form big ET-1 which is further processed to form the active peptide by endothelin-converting enzyme 16 .…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…However, the precise mechanism is still ambiguous. Although it has been reported that the three ETs are almost equipotent in producing transient vasodilation [3,4], it was also…”
Section: Introductionmentioning
confidence: 96%
“…Sarafotoxins (SRTs), having chemical structures similar to those of ETs, also consist of a novel cardiotoxic peptide family [2] and these peptides interact witla ET receptors [1]. A diverse set of pharmacological activities with different potencies exerted by ET/SRT family peptides [3][4][5][6] suggested the existence of ET/SRT receptor subtypes. We have reported that two distinct subclasses of ET receptors, namely, ET-l-specific and ET/SRT family-common receptors, are distributed in various proportions in human and porcine tissues [7].…”
Section: Introductionmentioning
confidence: 99%
“…ET consists of three isopeptides, termed ET-1, ET-2 and ET-3 (ETs), while their receptors are classified, both pharmacologically and molecularly, into ET A and ETB subtypes [2][3][4][5]. The ET A receptor has different affinities for the three ET isoforms in the order of ET-I>ET-2>>ET-3.…”
Section: Introductionmentioning
confidence: 99%